Use of a Simple Anthropometric Measurement to Identify Low-Birth-Weight Infants in Enugu, Nigeria - Ndubuisi Kennedy Chukwudi; Huldah Ijeoma Nwokeukwu MBBS, MPH, FWACP, FMCPH; Gilbert Nwadiakanma Adimorah MBBS, FMCPaed (SAGE Publishing, 2018)
Background . This prospective study was conducted to identify a suitable alternative to birth weight and establish its cutoff point to facilitate the identification of low-birth-weight (LBW) infants in Enugu, Southeast Nigeria. Methods . The study involved newborn babies within the first 48 hours of life. Five anthropometric measurements (head, chest, mid-arm and calf circumferences, as well as abdominal girth) were taken using a tape measure while supine length was measured with an aluminum infantometer. Birth weight was also recorded. Linear regression analysis was done to identify the measurement with the highest coefficient of determination with birth weight while its cutoff point was defined using a receiver operating characteristic curve. Standard statistical tests were used to determine the statistical significance of the findings. Results . The LBW prevalence for the study population was 21.41%. Chest circumference had the highest R 2 value of 0.83 for the general study population and 0.72 for the LBW infants. The identified cutoff point for chest circumference is ⩽30 cm. Conclusion . Chest circumference is the best alternative to birth weight in identifying LBW babies within the first 48 hours of life in this environment.